1976
DOI: 10.1042/bj1540225
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyruvate dehydrogenase and pyruvate dehydrogenase phosphate phosphatase activity in rat epididymal fat-pads. Effects of starvation, alloxan-diabetes and high-fat diet

Abstract: 1. Pyruvate dehydrogenase phosphate phosphatase activity in rat epididymal fat-pads was measured by using pig heart pyruvate dehydrogenase [32P]phosphate. About 80% was found to be extramitochondrial and therefore probably not directly concerned with the regulation of pyruvate dehydrogenase activity. The extramitochondrial activity was sensitive to activation by Ca2+, but perhaps less sensitive than the mitochondrial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

1976
1976
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 35 publications
5
50
1
Order By: Relevance
“…These values are similar to those obtained by Stansbie et al [7] (49%) but differ from those obtained by ourselves and others using gastrocnemius or mixed hindlimb musclese.g. Hennig et al [4] (15%), Hagg et al [10] (22%0), and Caterson et al [8] (68%).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These values are similar to those obtained by Stansbie et al [7] (49%) but differ from those obtained by ourselves and others using gastrocnemius or mixed hindlimb musclese.g. Hennig et al [4] (15%), Hagg et al [10] (22%0), and Caterson et al [8] (68%).…”
Section: Resultssupporting
confidence: 88%
“…This is due to difficulties with extraction and assay of the enzyme from this highly fibrous tissue. Indeed, reports of changes in °70PDHa have been variable both with regard to estimates of total PDH complex activity and %PDHa (compare [4,[7][8][9]). Despite this it has been reported that °70PDHa is reduced by starvation in gastrocnemius muscle [4,10] and that muscle PDH complex activity is increased by insulin [11].…”
Section: Introductionmentioning
confidence: 99%
“…min-' . g tissue-' were found which, allowing for differences in assay temperature, are very similar to those reported for rat liver [6,9,10]; in addition 16-17% of the activity was in the active state, again in good agreement with [9,10].…”
Section: Resultssupporting
confidence: 82%
“…Samples of liver, perirenal adipose tissde or placenta were removed as quickly as possible and frozen in liquid nitrogen. Preparation of tissue extracts and assay of 'initial' (PDHa) and 'total' PDH activity were carried out as described by Stansbie et al [6] except that the assays were performed at 37'C instead of 192 30°C. Protein concentration of the homogenates was determined by the method in [7].…”
Section: Materials Aud Methodsmentioning
confidence: 99%
“…49 Total PDHC activities in white adipose tissue were not measured in the present study. However, a previous study 13 reported that both active and total PDHC activities were depressed by high-fat feeding in epididymal fat pads of young male rats. Another study demonstrated that antecedent high-fat feeding prolonged the response of white adipose tissue PDHC to an intravenous glucose challenge in overnight-starved rats.…”
Section: Discussionmentioning
confidence: 82%